LightCycler® MRSA Advanced Test for Rapid MRSA Detection in Referral Patients Admitted to Intensive Care Units - Boonma, Paithoon; Hiranniramol, Sonchai; Thupvong, Kosin; Kukreja, Rapin; Vinitwatanakhun, Chuchart; Seanghiranvattana, Sawang; Wittayachanyapong, Siriporn; Tanyasittisuntorn, Pravich; Shinawong, Chanvit; Prakardvudhisarn, Piemsak; Suwanarit, Arisara; Kongkittimakul, Achara; et al. (The Bangkok Medical Journal, 2014)
OBJECTIVE: We studied the prevalence of Methicillin Resistant Staphylococcus Aureus (MRSA) nasal carrier in patients who were transferred and admitted to the intensive care unit (ICU). MATERIALS AND METHOD: By using LightCycler® MRSA advanced test for the direct detection of MRSA DNA in nasal colonization by polymerase chain reaction (PCR) and comparing to standard MRSA isolated from plates culture media. RESULTS: From December 2010 to May 2011, 100 patients were enrolled. They were referred to be admitted in ICUs of Bangkok Hospital Medical Center (BMC) (87), Samitivej Hospital Sukhumvit (12) and Bangkok Hospital Pattaya (1). Seventeen patients were excluded from the study. Of 83 patients, the light cycler MRSA test detected MRSA from an anterior nasal swab in 12 (14.5%) patients while concomitant plates culture grew MRSA in 10 (12.1%) (Kappa = 0.7913, 95% condence interval (CI) = 0.594-0.988). CONCLUSION: The LightCycler® MRSA advanced test is a diagnostic test for rapid MRSA detection. The test aids in the detection of hospital infection and in the control of MRSA infections by rapid detection, therefore identifying the appropiate and isolated patient whom has MRSA colonization particularly in high risk patients.